Evaluation of adverse reactions to the drug paclitaxel in patients with breast cancer in a municipal referral hospital - Moreira, Amanda Cristina Negri; Santos, Tamires Alves dos; Campanher, Ronaldo; Marini , Danyelle Cristine (Brazilian Journal of Implantology and Health Sciences, 2024)
Paclitaxel (PTX) is a naturally occurring antineoplastic drug originally isolated from the bark of the Yew tree (Taxus bevifolia). It is currently used to treat various types of cancer, particularly in the M phase of cell division, where it blocks the functioning of the mitotic spindle by stabilizing the microtubules, which are responsible for giving the cell shape through the cytoskeleton. Commercially known as Taxol®, PTX has low solubility in water and is sold in Cremophor solution, which can cause several adverse reactions, such as peripheral neuropathy and hypersensitivity reactions. This study consisted of an analysis of the use of the antineoplastic drug PTX, addressing its adverse reactions, as well as its influence on the quality of life of breast cancer patients treated with this drug. The study was a quantitative, exploratory and cross-sectional study, through a bibliographic review and application of a questionnaire to 52 patients who use the drug paclitaxel, in various cycles of chemotherapy at the Municipal Hospital “Dr. Tabajara Ramos” in Mogi Guaçu. Of the participating patients, (50%) are over 51 years old and only (1.9%) are between 20 and 30 years old, (38.5%) of them had been in treatment for a longer time, (92%) reported having had some adverse reaction and only (8%) did not, (83%) reported bone pain and/or muscle pain, (50%) presented changes in the exam that precedes chemotherapy with the taxane. Only (4%) of the participants had an immediate allergic reaction to the intravenous application, (2%) the taxane administration was interrupted and could not be administered on the same day, (67%) had dermatological reactions, (60%) felt weak and needed to rest at home after the taxane administration, (83%) did not have lesions in the oral cavity, only (17%) did not have any. It is concluded that the majority of the participants had adverse reactions, and that they were not only nausea, vomiting, diarrhea and hair loss as most people think when dealing with chemotherapy. Keywords: Chemotherapeutics. Breast cancer. Paclitaxel. Adverse drug reactions.